Accounting in Africa - Tauringana, Venancio; Mangena, Musa (Research in accounting in emerging economies ;, 2012)
The African context provides a unique environment for accounting research: the stage of economic and market development is low, corruption is rife and politics often meddles in corporate affairs. Such an environment can affect the nature of accounting and indeed the manner in which accounting is used, which makes accounting research in Africa important and interesting. The 10 papers in this volume were presented at the inaugural African Accounting and Finance Association (AAFA) in 2011 and are based on data from Ghana, Mauritius, Nigeria, Uganda and South Africa. Motivated by the AAFA vision, this special volume provides a source of rich data for academics, practitioners and policy makers with interest in accounting research in Africa to draw upon to inform accounting debate and help provide better understanding of accounting in Africa and beyond.